Hasil Belajar Kognitif Siswa SMP melalui Penerapan Model Pembelajaran Inkuiri Terbimbing pada Materi Hukum Archimedes - Mutiah, Mutiah (Jurnal Pendidikan Teknologi Informatika dan Sains, 2023)
Only 40% of the students who successfully completed the IPA program had learner outcomes that above the KKM threshold, which led to the current study's conclusion. In addition to that, the teacher still uses the conventional method. Based on the aforementioned problem, the aim of the study is to (1) understand the significance of the pengaruh that was identified after the model of in-depth instruction on the law of Archimedes was implemented in class VIII.3 at SMP Muhammadiyah 2 Pekanbaru. (2) Pengaruh signifikan terhadap hasil belajar kognitif siswa saat diterapkan model pembelajaran inkuiri terbimbing di kelas VIII.3 SMP Muhammadiyah 2 Pekanbaru. This study is an experimental study using a one-group pretest-posttest design. Every eighth-grade student at SMP Muhammadiyah 2 Pekanbaru, which is made up of three grades, is the populous participant in this study. Purposive sampling is a technique used in sample collection, and samples used in research studies.